Letter from William A. Guillory to J. W. Stout, December 31, 1975 - Guillory, William A. (1975)
Letter from William A. Guillory to J. W. (John Willard) Stout, nominating William M. Jackson (1936-) and William A. Lester, Jr. (1937-) for the Editorial Board for the Journal of Chemical Physics.
Keywords: Guillory, William A.; Jackson, William M., 1936-; Lester, William A., Jr., 1937-; Stout, J. W.; Chemists; African American chemists; Periodicals